Menumbuhkan Minat Usaha dengan Memanfaatkan Komoditas Lokal di Kelurahan Boja Kecamatan Boja Kabupaten Kendal - Teti Susilowati; Emy Susiatin; Juhanes Juhanes; Mieftakhul Fuady (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Boja Village is located in the center of Boja District, Kendal Regency. Its area is relatively large compared to other villages. With a large population, many businesses have developed in the area. Boja has significant potential for MSME development and economic growth. Most of the area is agricultural land, mostly planted with cassava. The purpose of this community service activity is to provide outreach by empowering women from the Family Welfare Movement (PKK) to foster entrepreneurial interest in Boja Village, Boja District, Kendal Regency. Cassava is a highly versatile commodity, capable of being used in a variety of food preparations, including as a substitute for wheat flour, to create a variety of ready-to-sell foods. By utilizing this commodity, it is hoped that women can start businesses to supplement family income and increase its economic value. Recognizing this potential, the Community Service team will conduct outreach activities, including entrepreneurship training, workshops on various processing innovations, and digital marketing for housewives in the area. The community service activity took place on Thursday, June 12, 2025, from 3:30 PM to 5:30 PM WIB (Western Indonesian Time). Twenty-three participants covered entrepreneurship, workshops, and digital marketing. They were highly enthusiastic about the activity. The outreach program demonstrated an increased understanding of entrepreneurship, skills, and interest in starting a business. Evaluation results showed an increase in understanding, exceeding 50%, after pre- and post-tests. The target output of this community service is publication in national journals, HKI videos, YouTube, and through mass media.